(untitled) (Dhaka University Journal of Biological Sciences, 2017)
An experiment was conducted to determine the effect of diazinon pesticide on some chemical properties of soil and to evaluate the accumulation of diazinon in Indian spinach (Basilla alba) under different doses of rice hull. Diazinon application had a positive effect to reduce the electrical conductivity (EC) of soil. Values of pH were found to decrease with the addition of diazinon. Diazinon had no effect on soil organic matter content although addition of rice hull increased organic matter content in soil with time. Plant analysis showed that the application of rice hull restricted the uptake of diazinon and continuously decreased with time. Therefore, rice hull could be used to control the uptake of diazinon pesticide by short duration vegetable crops. Dhaka Univ. J. Biol. Sci. 26(2): 125-131, 2017 (July)